Food Test at Warung X and Y Using Total Plate Count (Study on Food Safety for Female Santri Yogyakarta) - Alfi Makrifatul Azizah (Jurnal Berkala Kesehatan, 2022)
The goal of sustainable development point 2 is to end hunger by 2030 and one of its main targets is safe food. Food safety is one of the efforts to meet the food needs of female students at Komplek Q Yogyakarta. This study aims to determine the content of bacteria and the level of food safety bacteriologically in food stalls X and Y. The design of this research is descriptive observational with laboratory examination using total plate count (TPC). The food samples studied were incubated in the laboratory for 2x24 hours using PCA media to see the bacterial content. The findings are calculated using a colony counter and compared with the 2009 BPOM RI standards.Research result show that as many as 14 food samples tested there is 5 samples that are not meet the requirements for microbial contamination limits in food according toBPOM RI in 2009, namely: 1) egg stew Y=3,4x106; 2) long bean vegetable X=6,0x104; 3) green bean vegetable Y=2,6x104; 4) fried bakwan X=2,5x107; and 5) fried bakwan Y=1,2x107. Several types of food in stalls X and Y are indicated to be less biologically safe. So that special attention is needed from the government and boarding school administrators in the local area in tackling the problem of food consumption safety for students.